2022
DOI: 10.3389/fsufs.2022.1012813
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing the importance of protein quality in an era of food systems transformation

Abstract: A transformation of current food systems is needed to nourish the growing global population in more sustainable ways. To support this, some are advocating for a shift to plant-based or -exclusive diets. These recommendations – typically borne out of concerns for the environment – often fail to account for unintended nutritional consequences, which could be particularly pronounced for protein intake. While there is enough protein to meet current global needs, the issue of protein quality is often overlooked and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Proteins are chains of amino acids that are involved in almost every process in the body. The main role of proteins is to provide the body with the amino acids needed to synthesize new proteins [38]. According to the European Union Protein Strategy [39], meat and other animal products are the main source of protein for the majority of adults in the European Union, but plant-based protein sources are also gaining popularity.…”
Section: Content Of Total Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins are chains of amino acids that are involved in almost every process in the body. The main role of proteins is to provide the body with the amino acids needed to synthesize new proteins [38]. According to the European Union Protein Strategy [39], meat and other animal products are the main source of protein for the majority of adults in the European Union, but plant-based protein sources are also gaining popularity.…”
Section: Content Of Total Proteinmentioning
confidence: 99%
“…Protein is the dominant nutrient in human nutrition that is caused by the need to ensure the optimal level of essential amino acids directly affecting vital functions; since the body cannot store protein, it is supplied to the body exclusively through nutrition [38].…”
Section: Content Of Total Proteinmentioning
confidence: 99%
“…Several research studies have observed the significance of the protein requirement to the body [5,6]. This requirement is increasing globally due to the high population growth and the awareness of protein's positive impact on the body.…”
Section: Introductionmentioning
confidence: 99%
“…Population growth, rising life expectancy, and age-related diseases are future challenges that science must face. Not only because of a human population whose size is predicted to expand to nearly 10 billion people by 2050 [1,2] but also owing to the increasing number of diseases, such as cancer, obesity, and diabetes, it is time to devise ways of eating a healthy and sustainable diet [3,4]. Considering ethical, health, and environmental impacts of conventional meat and animal-product consumption, plant-based nutrition could be a promising alternative.…”
Section: Introductionmentioning
confidence: 99%